ROLE OF JALAUKAVACHARANA (HIRUDOTHERAPY) IN THE MANAGEMENT OF SCALP PSORIASIS - A CASE STUDY - Andhey, *Vijay Pratap; Tambe, Abhijit Laxman; Malavade, Hrishikesh Chandrakant; Tople, Prashant B (International Journal of Ayurveda and Pharma Research, 2016)
Psoriasis is a common, Chronic, inflammatory, multisystem disease of the Skin. Psoriasis localized to certain areas of the body like scalp, nails, palms and soles need special treatment modalities and it is very difficult to control the disease in these areas because of various reasons like unrealistic expectations of the patients, time consuming treatment approaches, cosmetic- non acceptability, non-compliance by patient. Scalp is the first site of Involvement in up to 25% of patients of Psoriasis. In Modern science, psoriasis is treated with Photo chemotherapy and Corticosteroids which has adverse side effects like hepatic & nephrotoxicity. However in Ayurvedic Texts use of Leech therapy is mentioned beneficial in the many skin disorders and also mentioned that the diseases treated with Raktamokshana has less chances of re-occurrence. This article covers the use of Leech therapy (Jalaukavachanrana) in a case of Scalp psoriasis where the patient undergone Jalaukavacharana therapy for 3 sittings in OPD without any supportive medications internally or any other therapies. The important observation found was there is a significant decrease in the characteristics like Erythema, Thickening, Scaling and True Area percent of the scalp affected by psoriasis. On a whole, Jalaukavacharana was found to be very effective even without any internal medications. If it is supported by internal medications we can expect better results in the management of Scalp Psoriasis.